Effect of Buzz Group Regarding Content Knowledge and Practice On Fistula Care for Patients with Hemodialysis among Second Year Baccalaureate Nursing Students - Sawant, Manisha V.; Jacob, Susan (Innovational: Journal of Nursing and Healthcare, 2024)
Aim: The aim of the study is to assess the knowledge and practice on fistula care for patient with hemodialysis among 2nd year Baccalaureate nursing students. Introduction: A quantitative approach with Quasi-experimental two group pretest posttest design was adopted with conceptual framework of J.W Kenny’s open system was used. Methodology: Data were collected from 96 second-year Baccalaureate nursing students to access knowledge using Structured Questionnaire, and Likert scale to assess practice through Objective Structured Practical Examination by Non-probability convenient sampling method. Pilot study followed by actual data collection was done and analyzed using descriptive and inferential statistics. Results: (1) Statistical analysis shows that pre-test mean knowledge score was score was 5.89 whereas the mean post-test score was 11.63. Wilcoxon signed-rank test gives P = 0.000 that has a highly significance as P < 0.001. Hence H01 is rejected. The Buzz group was effective in improving the knowledge regarding fistula care for patient with hemodialysis in the experimental group. (2) Statistical analysis shows that the posttest practice mean score was in the experimental group was 71.52 with a standard deviation of 2.99; whereas the control group mean score was 39.66 with standard deviation of 2.54. Wilcoxon signed-rank test indicate P = 0.000 that is < 0.05. Hence the Buzz group was effective in improving the knowledge and practice of fistula care for patient with hemodialysis. Conclusion: Finding revealed that buzz group is effective in improving knowledge and practice on fistula care for patient with hemodialysis among 2nd year Baccalaureate nursing students.